Hantu dan Bisnis Media; (Analisa Fenomena Tayangan Mistik di Media dengan Pendekatan Metode Komunikasi Terapan) - Hakiki, Kiki Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2019)
The focus of this paper is to examine the phenomenon of the rise of mystical shows in the media - both electronic and print media with a communication science theory approach namely the